Format and Content of the Package Design Safety Report for the Transport of Radioactive Material : specific safety guide. (Safety standards series ;, 2022)
"Requirements for the safe transport of radioactive material are established in IAEA Safety Standards Series No. SSR-6 (Rev. 1), Regulations for the Safe Transport of Radioactive Material, 2018 Edition. Packages intended for the transport of radioactive material have to be designed to meet applicable national and international regulations. For package designs that require approval by a competent authority, the documentary evidence of compliance with the applicable regulations is commonly known as package design safety report (PDSR). For package designs that do not require competent authority approval, a PDSR would also be an appropriate form of documentary evidence of compliance with the Transport Regulations. This Safety Guide provides recommendations on the preparation of a PDSR to demonstrate compliance of a package design for the transport of radioactive material with the Transport Regulations. This Safety Guide is intended for use by applicants for approval of package designs (when package designs are subject to competent authority approval) as well as by package designers and/or consignors (when package designs do not require competent authority approval). Regulators will benefit from the common structure for the competent authority assessment process, and designers and consignors will find a consistent approach to justify the compliance of a package design with the regulatory requirements."--Publisher's description.